Gas sensing response of metal oxide layers based on Cox Oy with lithium ions - Yu. A. Stenkin; D. V. Sokolov; K. E. Ivlev (Омский научный вестник)
The gas response of layers based on lithium-doped cobalt oxides with different Li2 O/Cox Oy ratios is investigated. The synthesis conditions of oxide composites and the structural analysis of the obtained layers by scanning electron microscopy are presented. It is found that composites with the ratio of the initial components 1:1 have selectivity to formaldehyde, and with the ratio 3:2 — to nitrogen dioxide.